2011
DOI: 10.1007/s00436-010-2228-9
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito larvicidal activity of citrus limonoids against Aedes albopictus

Abstract: Citrus limonoids, nomilin and limonin, were used for larvicidal assay against Aedes albopictus utilizing WHO methodology. LC(50s) were 305.83, 176.08, and 136.07 μM for nomilin and 850.09, 600.72, and 407.09 μM for limonin after 24, 48, and 72 h, respectively. LT(50) assays exhibited that Savage citrange oil was the best at all concentrations (400, 500, 600, and 700 ppm) while Fairchild and Cassa grande were the weakest oils at 400 ppm, but at 500, 600, and 700 ppm, Carrizo citrange remained at the bottom with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 26 publications
0
21
0
2
Order By: Relevance
“…Our results are in agreement with those reported by Chaithong et al (2006) and Islam et al (2003) against C. quinquefasciatus. Hafeez et al (2011) reported that the liminoids from citrus showed the highest larvicidal activity against A. albopictus.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in agreement with those reported by Chaithong et al (2006) and Islam et al (2003) against C. quinquefasciatus. Hafeez et al (2011) reported that the liminoids from citrus showed the highest larvicidal activity against A. albopictus.…”
Section: Discussionmentioning
confidence: 98%
“…The unbalanced solubility profile of the latter may explain the relatively low number of studies on their respective biological activities which are hampered by difficult isolation from natural sources and poor pharmacokinetics. Analgesic [45], anticancer [46][47][48][49][50][51][52][53][54][55][56][57][58][59], anti-inflammatory [45,[60][61][62], antibacterial [63,64], antioxidant [4,65,66], antiviral [67], larvicidal [68,69] Anticancer [46,47,58,59,70], anti-hyperglycemic [71], anti-inflammatory [25,62], antioxidant [4,65,66], antiviral [67], larvicidal [68,69] …”
Section: Chemistry and Classificationsmentioning
confidence: 99%
“…The larval population was reared on TetraMin Tropical (Tetra TM). Adults were reared in steel cages and males were provided with 10% sucrose solution, while females were fed on blood of white rats (albino) [12] . Eggs were laid in plastic cups lined with filter paper then they were separated and shifted to rearing trays.…”
Section: Entomopathogenic Fungusmentioning
confidence: 99%